The Game of Youth: Forms of Civic Engagement among Youth around the World - Anuar Kamri, Khairol; Abd Hamid, Aizathul Hani (International Journal of Psychosocial Rehabilitation, 2019)
Civic engagements are important to make democracy sustainable. The forms of its activities are increasing from day to day, but the traditional forms of political participation remain the most fundamental forms in civic engagement. This article presents a variety of forms of civic engagement among youth that are found in the existing literature about youth civic engagement around the world. The systematic review process is guided by the PRISMA Statement Review Method. The existing literature was rigorously searched by using Scopus as the main database. The result was then categorized into nine themes, which are organizational membership, volunteerism activities, online participation, electoral and political involvements, social cohesion, training and development, intellectual discourse, decision-makers, and civic attitude. These nine themes are elaborated to the 38 sub-theme of civic engagement activities. This article is the collection of all themes about civic engagement forms that existed around the world in six years of latest research. Previous research usually just focused on a certain theme and may ignore other important forms of civic engagement. The finding from this systematic literature review article discovers varieties of forms of civic engagement activities that are close to the youth interest. By choosing the right forms, it will help develop good citizen behaviour among youth and lead to peacebuilding in society. Future literature is recommended by examining the objective of each form and identifying which form is suitable for each country's ideologies.